2017
DOI: 10.18632/oncotarget.17700
|View full text |Cite
|
Sign up to set email alerts
|

Correlation ofHAMPgene polymorphisms and expression with the susceptibility and length of hospital stays in Taiwanese children with Kawasaki disease

Abstract: Kawasaki disease (KD) is a form of systemic vasculitis. Regarding its pathogenesis, HAMP gene encoding hepcidin, which is significant for iron metabolism, has a vital function. In this study, we recruited a total of 381 KD patients for genotyping. Data from 997 subjects (500 subjects from cohort 1; 497 subjects from cohort 2) were used for analysis. Using TaqMan allelic discrimination, we determined five tag SNPs (rs916145, rs10421768, rs3817623, rs7251432, and rs2293689). Treatment outcome data related to suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In our previous studies, we have shown that the changes in plasma hepcidin levels after IVIG treatment in KD patients were correlated with CAL formation and IVIG resistance [14]. We also demonstrated that prior to IVIG administration, the hepcidin levels were positively correlated with AST and ALT and negatively correlated with albumin in KD patients [15]. However, few studies have investigated the regulation of HAMP genes at the epigenetic level.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous studies, we have shown that the changes in plasma hepcidin levels after IVIG treatment in KD patients were correlated with CAL formation and IVIG resistance [14]. We also demonstrated that prior to IVIG administration, the hepcidin levels were positively correlated with AST and ALT and negatively correlated with albumin in KD patients [15]. However, few studies have investigated the regulation of HAMP genes at the epigenetic level.…”
Section: Discussionmentioning
confidence: 87%
“…Hepcidin, which is encoded by the HAMP gene, is well known to play a key role in the inflammation-associated anemia mechanism [12,13]. Furthermore, we have demonstrated that hepcidin levels are elevated in KD patients [14,15]. Following IVIG administration, KD patients' plasma hepcidin levels significantly decreased, and their changes were related to IVIG treatment resistance and CAL formation development [8,14].…”
Section: Introductionmentioning
confidence: 79%
“…Our previous study focusing on patients with Kawasaki disease also showed that plasma hepcidin levels both before and after IVIG treatment were positively correlated with patients' length of hospital stays (R Z 0.217, p Z 0.046, and R Z 0.381, p < 0.0001, respectively). 34 In cardiac surgical patients, plasma hepcidin concentration related to outcome and preoperative anemia was shown to be associated with prolong intensive care unit stays. 35,36 Elevated hepcidin levels indicates an iron deficiency and anemia that are often associated with an increased hospital stay length.…”
Section: Discussionmentioning
confidence: 99%
“…The three active DNA methyltransferases are DNMT1, DNMT3A, and DNMT3B, and three DNA demethylase, TET1-3, have been identified in mammals 7, 8. We have previously shown considerably increased mRNA expressions in toll-like receptors 9, hepcidin 10, 11, matrix metalloproteinases 12, inflammasome sensors of NOD-like receptors 13, and hypomethylation at the gene promoters of these genes, as well as that IVIG treatment can drastically alter these methylation patterns in the WBC cells of KD patients 9-14. Consistently, we have demonstrated that 87.8% of the most of the significant CpG markers between KD patients and controls are hypo-methylation of CpG markers by genome-wide screening on DNA methylation patterns with Illumina HumanMethylation450 (M450K) Bead-Chip microarray assay 15.…”
Section: Introductionmentioning
confidence: 91%